DEKONSTRUKSI KOMUNIKASI POLITIK DI ERA DIGITAL (Studi Analisis Wacana Kritis Fairclough) - Putri Retnosari; Rizal Mustansyir; Hastanti Widy Nugroho (DIA: Jurnal Administrasi Publik, 2019)
Research entitled "Fairclough’s Critical Discourse Analysis in exposing the Crime of Political Communication in The Digital Ag" is motivated by crime issues that have developed into various social crimes, such as cyber crime, psychological crime, economic crime, and political crime. In the digital age, the crime of political communication is new because this form of crime is sublimated in e-commerce which tends to appeal to all ages. Critical discourse analysis offers a critical perspective in addressing the latest phenomena facing humans in the Digital Age. Especially the phenomenon of technology whose development is increasingly fast and uncontrollable. The purpose of this study is to reveal various forms of political communication crime through critical discourse analysis. The method used in this research is the library method. The results showed that the crime of political communication in the Digital Age occurred through the medium of the Digital Market as a medium of political communication